Fenomena Penghentian Operasional Holden di Australia - Naufal Ridho Maulana; Hermini Susiatiningsih; Muhammad Faizal Alfian (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The discontinuation of Holden's operations was caused by the unfriendly policy of the Australian government. The fall of an industrial entity are influenced by the manifestation of the government's interest upon the economy wheel. Australia's national interest in its strategy of international trade oriented towards the energy, minerals and agriculture sector has had dire consequences for Holden. In addition, Australia's commitment to the United Nations Economic Commission for Europe (UNECE) for environmentally friendly vehicles has changed the orientation of its national automotive industry. Furthermore, Donald Trump's isolationism policy towards the Trans-Pacific Partnership (TPP) has indirectly killed Holden. This study uses four conceptual frameworks in the form of International Political Economy Theory, the Concept of Government Decision Making on the Market, Free Trade Policy, and the Concept of Government Policy on Industrial Operations. Based on the research that has been carried out, this proves that the political dimension will always affecting an economic entity. The Australian government has legitimized its national automotive industry through a political decision-making process.Keywords: Holden, Manifestation of Interest, International Trade, Government Legitimacy